Content validity of the Spanish language Gaokao test: Taking the tests from 2018 to 2020 as an example - Li, Lujia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This study investigates the content validity of the Spanish language Gaokao test through the exams from 2018 to 2020, together with the national Spanish curriculum and the Gaokao explanation document. The degree of correspondence between what is examined in each test task and the requirements of the curriculum and the examination explanation document is evaluated. The initial result shows that the Gaokao of Spanish has evidence of validity, except for the task on lexicon and grammar and the translation whose design is to be optimized.